Do disco à roda: a construção do pertencimento afrobrasileiro pela experiência na festa Negra Noite - Campos, Deivison Moacir Cezar de (Universidade do Vale do Rio dos Sinos, 2014)
The present paper investigates the structure of the Afro identity through the experience in Black music parties. The thesis supports that the social interactions of the black community, held around collective consumption of music, which were traditionally arranged by the structure of sacred or profane circles have been affected by the media. Such fuss caused the constituent elements of identity, deterritorialized by the movements of diasporas and previously shared only by personal interaction in the circles to be spread by the sound media as well. Thus, the collective consumption of music recorded enables new forms of interaction, the communication experience. From the articulation of experience and ownership concepts, relating them to the elements of traveller culture of the Black Atlantic and being the circle, present in different African and diaspora cultural events, such as synthesis elements, a theoretical and methodological study is proposed, which seizes the spatial, cultural and media dynamics involved in the process. The structure of an African-media ambiance, through the relation of the bodies in performance, with the recorded music and sound and lighting equipment enables different territoriality and temporality to compete, taking, mediated by the collective memory, to the presentification of the Afro. The party Negra Noite was the place of observation, through an ethnographic research. The music recorded enters the party in the circuit of cultural consumption of black music, while the mediation of the collective memory connects the party to the recent tradition of Black Porto dances and to the long lasting tradition of the Black Atlantic.
Keywords: Pertencimento afro-brasileiro; Negra Noite; Atlântico Negro; Black music; Performance; African-brazilian´s characteristics; Black Atlantic; Black music; ACCNPQ::Ciências Sociais Aplicadas::Comunicação